(untitled) (Journal of Education and Development, 2019)
A Rwandan saying literally articulates that the optimal development of a woman is vital to the development of the family. However, in Rwanda, women remain disadvantaged in terms of participation in top job hierarchies. This study explored upward mobility among educated women in the Public Sector in Rwanda. The study established that women’s lack confidence to compete for higher-level positions is the main cause of gender discrepancies in top-level positions (89.7%). Women rush to get married instead of going for higher Degrees (Master’s and PhD) (79.4%) and fewer women complete Bachelor’s Degree while the higher Degree is the screening device to access top-level positions (81%). The Main implications of this gender disparity are unequal distribution of income (95.6%) and low salary for women (75%). It was concluded that gender disparity in qualifications in top-level positions in Rwanda’s Public Sector deserves serious consideration to be alleviated.